Case Report: A Variant Non-ketotic Hyperglycinemia With GLRX5 Mutations: Manifestation of Deficiency of Activities of the Respiratory Chain Enzymes - Feng, Wei-xing; Zhuo, Xiu-wei; Liu, Zhi-mei; Li, Jiu-wei; Zhang, Wei-hua; Wu, Yun; Han, Tong-li; Fang, Fang (Frontiers in Genetics, 2021)
Abstract Objective Variant non-ketotic hyperglycinaemia (NKH) is a rare disorder characterized by variable clinical, biochemical, and imaging features. The variant form of NKH is rare and characterized by variable clinical, biochemical and imaging features. Subjects Herein, we report a girl with variant NKH with two mutations in glutaredoxin 5 (GLRX5), which has been described in only three patients. Results The clinical and biochemical phenotypes of the patient are also described. She suffered from developmental retrogression associated with spasticity, developmental delay, anaemia and optic atrophy. The leukodystrophy or mitochondrial leukoencephalopathy were used to designate these disorders. An increased T2 signal from the medulla oblongata to the C6 spinal region was also observed on spinal cord MRI. Tandem mass analysis of a dried blood sample revealed elevated levels of glycine. The patient has two compound heterozygous mutations (c.151_153 del AAG and c.196C>T) in the GLRX5 gene. The c.196C>T mutation led to a stop codon (p.Q66*) that has not been reported previously. Activities of Mitochondrial respiratory chain (MRC) complexe II+III in the patient’s fibroblasts was abnormal. Conclusions We present the case of a girl with variant NKH who manifested spasticity and bilateral leukodystrophy. The patient had a deficiency of a respiratory chain enzyme, and this is the first report. Genetic testing is important for physicians to evaluate suspected variant NKH patients and to provide proper genetic counselling.